Smartphone Time Machine: Tech-Supported Improvements in Time Perspective and Wellbeing Measures - Mossbridge, Julia; Johnson, Khari; Washburn, Polly; Williams, Amber; Sapiro, Michael (Frontiers in Psychology, 2021)
Individuals with a balanced time perspective, which includes good thoughts about the past, awareness of present constraints and adaptive planning for a positive future, are more likely to report optimal wellbeing. However, people who have had traumas such as adverse childhood experiences (ACEs) are likely to have less balanced time perspectives and lower overall wellbeing when compared to those with fewer or no ACEs. Time perspective can be improved via time-travel narratives that support people in feeling connected to a wise and loving future version of themselves, an approach that has until now only been provided in counseling contexts. Our team used an iterative inclusive design process to shape a scalable time-travel narrative tool – a responsive and progressive web application called Time Machine. Among other functionalities, Time Machine allowed people to record and listen to messages as if they were from and to their past and future selves. Using pre-planned as well as post-hoc analyses, we analyzed quantitative and qualitative data from 96 paid design partners (participants) who were taken through a 26-day pilot study of the technology. Among other effects, the results revealed: 1) high engagement throughout the design process, 2) improvements in self-reported time perspective and overall wellbeing scores that were greater for those using Time Machine during an optional-use period, 3) twice as much improvement in overall wellbeing scores for design partners with high ACEs (16%) versus low ACEs (8%), and 4) feelings of unconditional love apparently mediating the relationship between scores on time perspective and overall wellbeing measures. We discuss the limitations of these results as well as implications for the future role of spiritually-informed scalable time-travel narrative technologies in healthcare and wellness.